Qualification of an enzyme-linked immunosorbent assay for quantification of anti-Vi IgG in human sera - Carducci, Martina; Massai, Luisa; Lari, Elisa; Semplici, Bianca; Aruta, Maria Grazia; De Simone, Daniele; Piu, Pietro; Montomoli, Emanuele; Berlanda Scorza, Francesco; Grappi, Silvia; Iturriza-Gómara, Miren; Canals, Rocio; et al. (Frontiers in Immunology, 2024)
Effective vaccines against Salmonella Typhi, targeting the Vi capsular polysaccharide, have been developed and are being introduced into routine immunization in endemic countries. Vi conjugated vaccines are also being tested in new multi-component vaccine formulations. Simple, highthroughput and cost-effective assays to quantify Vi-specific IgG in clinical sera are needed. In this study we present the development and qualification of a new anti-Vi ELISA with continuous readout, which expresses results as ELISA Unit/mL (EU/mL). We have qualified the assay in terms of precision, linearity and specificity, demonstrating performance in line with a commercially available anti-Vi ELISA. We have also calibrated the assay against the 16/138 anti-Vi international standard and established conversion factor between EU/mL and international units/mL, to allow comparability of results across studies. In summary, this new assay met all the suitability criteria and is being used to evaluate anti-Vi responses in clinical studies.